DIATOMS USED IN ASSESSING WATER QUALITY IN 3 BASIN OF THE PROVINCE OF SAN LUIS (ARGENTINA) (Natura Neotropicalis, 2018)
It is known to use algae as bioindicators of organic contamination in aquatic ecosystems. The objective of this study was to assess the quality of water in three basins of San Luis province by applying the Pampean Diatoms Index (IDP). The 3 basins of the province were studied for one year. Epilitic diatoms samples were taken. Upstream sites recorded the lowest IDP levels, which indicates a good to acceptable quality and shows a better structuring of the diatom taxocenosis. The sites of the middle and final sections hold species that prefer environments rich in nutrients (bad quality). The replacement of less sensitive species by others more tolerant to higher organic concentrations was observed. IDP values showed deterioration of water quality downstream, which indicates anthropic activity.
Keywords: diatoms; bioindicators; Mountain Rivers